Peningkatan Kapasitas Produksi Bumbu Bali â€œNepaonâ€ Suka Wirang Desa Buki - Suniantara, I Ketut Putu; Suwardika, Gede; Sopandi, Agus Tatang; Masakazu, Kadek; Wijaya, I Gusti Ngurah Satria (STMIK Royal, 2023)
The Balinese spice